PERANGKAT LUNAK JAJAK PENDAPAT (VOTING) BERBASIS SHORT MESSAGE SERVICE (SMS) GATEWAY DAN WEB - Novendra Adisaputra Sinaga; Andi Setiadi Manalu; Benjamin Albert Simamora (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2020)
One of the characteristics of democracy is characterized by direct elections. Nowadays the role of technology greatly affects all aspects of life because it is more effective and accurate. Electronic voting or e-voting is the usual form of voting used for general elections and polls using electronic media. The shift in the conventional election process in today's technological era utilizes the media for polling, one of which is short message service (SMS). The use of Short Message Service (SMS) technology can now be utilized for voting because it is supported by many factors including availability, speed, security and accuracy of data generated. Voting Based on Short Message Service (SMS) and relatively cheap costs so as to make it easier for users, both voting participants and voting implementers, to be more optimal.